Analisis Statistik Chi-Square Terhadap Efektivitas Suplemen Tablet Zat Besi dalam Meningkatkan Kadar Hemoglobin - Dian Mustofani; Hariyani Hariyani; Rahmawati Erma Standsyah (UJMC (Unisda Journal of Mathematics and Computer Science), 2025)
This study aims to evaluate the impact of consuming iron supplementation tablets (TTD) along with milk on hemoglobin levels among adolescent girls, using the Chi-Square statistical analysis approach. A quasi-experimental design with a pretest-posttest control group was applied. The subjects consisted of 58 respondents, divided into two groups: intervention (TTD + milk) and control (TTD only). Hemoglobin levels were measured before and after the intervention and categorized as "increased," "decreased," or "unchanged" for the purpose of Chi-Square analysis. The Chi-Square test was conducted both manually and using SPSS version 25. The manual calculation, based on the formula , yielded a value of approximately with 2 degrees of freedom. The SPSS analysis showed a Pearson Chi-Square value of 35.714 with a significance level of 0.000 (p < 0.05), indicating a significant relationship between the type of intervention and the change in hemoglobin levels. These findings support the notion that consuming iron supplements together with milk may inhibit iron absorption, resulting in a decrease in hemoglobin levels. Thus, the Chi-Square analysis demonstrates the categorical effect of the intervention on hemoglobin status.